A Clinical Study Investigating Whether the Tongue-Out Position Improves the Quality of the Anatomical Appearance of the Pharynx on CT Imaging - Wu, Jin-Long; Ge, Rui-Gang; Tang, Guang-Jian (Frontiers in Surgery, 2021)
Objective To evaluate the effect of using the tongue-out position on the quality of the anatomical appearance of the pharynx on computed tomography (CT) images. Methods The data from enhanced CT thin-section images of the head and neck in 119 cases scanned were retrospectively analyzed. The cases were divided into two groups: the tongue-out group (63 cases) and non-tongue-out group (56 cases). Two observers separately evaluated the anatomy of the soft palate, uvula, palatine tonsils, epiglottis, epiglottic fossa, pyriform fossa, arytenoid folds, and tongue on all images. In the case of data that satisfied the normal distribution, the significance of the difference in the average scores between the two groups was tested using an independent samples t-test with a value of p > 0.05. In the case of data that did not satisfy the normal distribution, the Mann–Whitney U test was adopted to test the significance of the difference in the average scores between the two groups using a value of p < 0.05. The number of cases with swallowing artifacts on the CT images in both groups was statistically analyzed and determined whether the difference in the incidence of artifacts between the two groups was significant. Results The Kappa test showed good consistency between the two observers scoring of the soft palate, uvula, epiglottis, epiglottic fossa, pyriform fossa, aryepiglottic folds, and tongue. The image scores of the soft palate, uvula, epiglottis, epiglottic fossa, and tongue in the tongue-out group versus the non-tongue-out group did not satisfy the normal distribution. The Mann–Whitney U test showed that the differences in the image scores between the two groups were statistically significant in all cases (p < 0.05). The incidence of swallowing artifacts in the tongue-out group and the non-tongue-out group was 15% and 32%, respectively. The result of the chi-square test showed that the difference in the incidence of swallowing artifacts between the two groups was statistically significant (p = 0.037). Conclusion The tongue-out position facilitated an improvement in the CT appearance of pharyngeal anatomy and was associated with a reduction in the incidence of swallowing artifacts.